Actually Existing Commons: Using the Commons to Reclaim the City - Newton, Caroline (2022)
In Paraisópolis, a slum in São Paulo (Brazil) housing over 100.000 inhabitants, the Covid crisis seemed to have less of a death toll (0,0217%) than in other areas of the city (an average of 0,0652% as of May 2020); or at least it did at first. The sense of community in the area is strong, leading to many community initiatives and organisations to rise to the challenge of combating the pandemic with little help from the authorities. The community’s initial efficient response to the Covid crisis relied heavily on self‐reliance and self‐organization to mobilise common resources. Despite their later failure in containing the virus, the community’s response to the pandemic is exemplary of a well‐known phenomenon: how communities are able to mobilise the commons to create general welfare. The commons concept is used in this contribution to help us better understand slum governance and the power and limitations of community reliance. At the same time, we aim to refine our understanding of the commons as a contentious category rooted in agonistic relationships instead of the romanticised leftist social imaginary that views the commons as purely anti‐capitalist. Thus, we explicitly argue for a view of the commons and commoning that transcends the narrow “Leftist imaginary” of the commons as egalitarian, inclusive, anti‐capitalist, horizontal, and as expressions of sharing (and caring), and instead views the commons as embedded in everyday realities, where commoning practices emerge as practises that support the reproduction of (social) life.